Translations as Sources for the Press in the Nineteenth Century: The Case of the Gaceta de Caracas - Navarro, Aura (Íkala, Revista de Lenguaje y Cultura, 2010)
This article studies the influence of translations published in the Gaceta de Caracas during the Independence and the First Republic of Venezuela. The study consisted of three stages: 1) identification of translations; 2) comparative analysis between source texts (STs) and target texts (TTs); and 3) analysis of translation strategies. As a result, English is the most translated language in the gazette, given that the majority of source texts were taken from American and British newspapers. The content of the translations is largely political; all translations are anonymous. We observed the use of summary and periphrasis; literal translation was also a frequently used translation technique. Notably, appropriation was utilized as a translation strategy in half of the translations. To sum up, translation in the Gaceta de Caracas contributed to the consolidation of Venezuelan independence and the creation of the First Republic of Venezuela due to the use of appropriation combined with the political purposes of the translators. Received: 06-09-09 /Accepted: 19-11-09 How to reference this article: Navarro, A. (2010) Las traducciones como fuentes para la prensa en el siglo XIX: el caso de la Gaceta de Caracas. Íkala 15(1), pp.15-43.